Completive con reggenza nominale e verbonominale nell'italiano dei primi secoli - Frenguelli, Gianluca (Verbum – Analecta Neolatina, 2002)
This paper will analyse the uses of two completive constructions. One is of the ‘ricordanza che' variety. Here the completive is linked by che to a NS such as ricordanza, parola, promessione, segno and so on. The other is of the ‘aver novella che' variety. In this case the completive is governed by a VS composed of a verbal operator + noun generally indicating a locutionary act (bando, novella, preghiera, promessa, sentenza, etc.). These two kinds of completive constructions give rise to numerous implementations in Old Italian, the sheer number of which supports the claim that one of the most striking characteristics of early Italian prose is its plasticity.